Chia seeds nutritional value and its effect on serum glucose and cholesterol concentration in rats - Dr. Nawal H. Sebo (Polytechnic Journal)
The purpose of this study was to determine the major nutrients in chia seeds, the amino acid content of protein, the fatty acid content of extracted oil, and to investigate the effects of seeds consumption for 5 weeks on glucose and lipids levels in rat‘s blood. The results showed each hundred grams of chia seeds contains (3.76, 24.61, 35.75, 31.03, 21.12 and 4.66gm) moisture, protein, fat, total carbohydrates, crude fiber and ash respectively with 3.80mg of vitamin C. The result of amino acid analysis was indicates glutamic acid, asparagine, arginine from nonessential and tryptophan, phenylalanine from essential amino acids to be main components of seeds protein and represent of 3.264,3.300 ,2.550 and 1.858, 1.148gm/100gm sample, respectively. The analysis of fatty acid composition, allowed the quantification of twenty seven fatty acids. Unsaturated fatty acids and, in particular, linoleic and α-linolenic acids, were predominant in which there content were 18.233 and 50.641%,respectively,while palmitic acid was the major saturated fatty acid found in seeds and comprised 9.218% of total lipid. Also The effects of chia seeds on glucose levels and lipid profiles of rat serum were investigated, sugar, triglycerides and total cholesterol level in rats blood were significantly lower (P<0.05) and high density lipoprotein level was significantly higher (P<0.05) in the group of rats fed on chia seeds compared with control group.